Postpartum Depression Screening for Mothers of Babies in the Neonatal Intensive Care Unit. Issue 6 (November 2021) - Berns, Hannah M.; Drake, Diana
Abstract: Background: Postpartum depression (PPD) is a prevalent, yet underidentified, problem among mothers with babies in the Neonatal Intensive Care Unit (NICU). Postpartum depression can result in immediate and long-term consequences for mother and baby. Screening, followed by early intervention, is critical for improvement and resolution. The purpose of the project was to initiate early screening for PPD among a high-risk population to identify and refer for early treatment. Methods: A screening and referral protocol was implemented using the Edinburgh Postnatal Depression Scale (EPDS), with consults as indicated to an onsite licensed professional clinical counselor. The nurse on the care team was responsible for initiating the screening after 2 weeks postpartum and placing a mental health referral as needed. Retrospective medical record reviews were conducted to determine whether timely screening was implemented among eligible mothers, and if referrals were made for those at-risk based on EPDS score. Results: Twenty-four percent of women screened were at increased risk for PPD based on their EPDS score, approximately double that of the general population (12.5%). All women with a positive screen had a referral placed and were seen by the licensed professional clinical counselor within 3 days. Clinical Implications: This project recognizes the importance of an interdisciplinary care approach and highlights the need for early identification and treatment for PPD among mothers with babies in the NICU. The project can guide future initiatives to increase the use of screening in the inpatient setting, to detect PPD during its early and more treatable stages. Abstract : Mothers of babies in the neonatal intensive care unit are at greater risk for postpartum depression than mothers of healthy newborns. Screening mothers for postpartum depression while their babies are in the neonatal intensive care unit may be an effective way to avoid missing mothers who are experiencing this very common complication of childbirth. A quality improvement project is presented with details of initiating screening and efficacy of the process.